2013
DOI: 10.1111/jhn.12115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intrauterine and post‐natal nutritional determinants on blood pressure at 4 years of age

Abstract: Interventions focusing on cardiovascular health in young women during pregnancy and their children should be considered to reduce cardiovascular diseases risk factors in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…Normia et al . () reported that, in a small cohort of mother–child (4‐year‐old) pairs, higher maternal carbohydrate intake was associated with higher childhood systolic blood pressure and higher childhood systolic blood pressure was noted in offspring exposed to lowest or highest tertiles of maternal fat intake during pregnancy. A longer‐term follow up of Scots aged in their 40s for whom maternal food intake data were available also provided evidence that maternal intake could be a driver of intrauterine programming (Campbell et al ., ).…”
Section: Nutritional Programming During Foetal Developmentmentioning
confidence: 99%
“…Normia et al . () reported that, in a small cohort of mother–child (4‐year‐old) pairs, higher maternal carbohydrate intake was associated with higher childhood systolic blood pressure and higher childhood systolic blood pressure was noted in offspring exposed to lowest or highest tertiles of maternal fat intake during pregnancy. A longer‐term follow up of Scots aged in their 40s for whom maternal food intake data were available also provided evidence that maternal intake could be a driver of intrauterine programming (Campbell et al ., ).…”
Section: Nutritional Programming During Foetal Developmentmentioning
confidence: 99%
“…One cross‐sectional study reported high intakes of vitamin B 12 and folic acid to be associated with reduced BP in children . Maternal dietary characteristics such as pre‐natal fat intake and pre‐natal carbohydrate intake (between 270 and 447 g) were both associated with higher BP in one longitudinal study . Complementary feeding (time of introduction of solid food) lower than 5 months or higher than 6 months and being malnourished were also both associated with higher BP.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review comprised three articles about intervention studies, [17][18][19] of which two articles used data from the same RCT and 16 articles about observational studies, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] covering 12 mother-child cohorts ( Table 2). During the offspring follow-up, one of the intervention studies did not examine their data as intervention v. control group but combined both groups.…”
Section: Selection Of Articles and Study Characteristicsmentioning
confidence: 99%
“…During the offspring follow-up, one of the intervention studies did not examine their data as intervention v. control group but combined both groups. 17 There were 16 articles reporting on the association of maternal diet during pregnancy with offspring's cardiovascular health [17][18][19][20][21][22][23][25][26][27][28][29][30][33][34][35] and three articles reporting on the association of maternal physical activity during pregnancy with offspring's cardiovascular health. 24,31,32 No studies included both maternal diet and physical activity in one paper, although the association T. M. van Elten et al with both maternal exposures was studied in the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort at the same child age.…”
Section: Selection Of Articles and Study Characteristicsmentioning
confidence: 99%